Short-Term Stressor Effects of Water Deprivation Prior to the Onset of Lay on Subsequent Reproductive Performance of ISA Brown Pullets - Nirat Gongruttananun; Ratana Chotesangasa (Agriculture and Natural Resources, 2005)
The influence of water deprivation prior to the onset of production on sexual maturity and subsequent reproductive performance was investigated in commercial pullets. Three hundred 16-weekold ISA Brown pullets were used in this study. The birds were housed in cages (100 cages of 3 birds/cage) situated in an open sided poultry shed and randomly divided into three treatment groups. The 3 groups were 1) control (received feed with water at all times) 2) dehydrated and 3) dehydrated+NH4Cl. Following an acclimatization period of 4 weeks, the birds in all groups were placed on a commercial layer ration and the treatments began. In the dehydrated and dehydrated+NH4Cl groups, the drinking water was removed completely from the pullets for 48 hours of dehydration but feed available at all times. The water was then returned to the birds following the water withdrawal period, and thereafter until the end of the trial. The pullets in the dehydrated+NH4Cl group were fed on the layer diet supplemented with 1%NH4Cl throughout the experimental period. It was found that feed intake dropped rapidly, by approximately 50%, when the birds were subjected to water deprivation. Neither age at first egg nor at 50-60 % of production was influenced by the interruption of drinking water supply. Little difference in egg weight at first egg was noted between the dehydrated birds and the normally hydrated hens. Pullets deprived of water were slower coming into egg production especially during the first 2 weeks of production period, however, thereafter egg production was similar among all treatment groups with numerical advantages for the normally hydrated hens. There were no carryover effects of water deprivation on subsequent egg weight, albumen weight, Haugh units, yolk weight or yolk color throughout the entire 12 weeks of the test. Body weights were not different either before the treatment or at the end of the study (P>0.05). The results might be interpreted as indicating that an interruption of drinking water supply for 2 days prior to the commencement of egg production induced transient effects of nutrient deficiency resulted in retardation of reproductive development. The acidified layer ration failed to show any positive effects on reproductive performance for the first 12 weeks of lay. The pullets, however, appeared to overcome the detrimental effects as they approached sexual maturity.